2009
DOI: 10.1186/1471-2326-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Profile of hematological abnormalities of Indian HIV infected individuals

Abstract: Background: Hematological abnormalities are a common complication of HIV infection. These abnormalities increase as the disease advances. Bone marrow abnormalities occur in all stages of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
110
6
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(158 citation statements)
references
References 9 publications
26
110
6
5
Order By: Relevance
“…This reduced value may be due to the fact that immune systems of those not on antiretroviral therapies are more depressed or immunocompromised than the immune system of those not on ART, hence the lower value of PCV observed in them. This finding support the fact that ART improves Hematological parameters, hence the improved level of PCV on those on ART than on those not on ART (Amegor, 2009(Amegor, et al, 2009Byomakesh et al, 2009). …”
Section: Discussionsupporting
confidence: 78%
“…This reduced value may be due to the fact that immune systems of those not on antiretroviral therapies are more depressed or immunocompromised than the immune system of those not on ART, hence the lower value of PCV observed in them. This finding support the fact that ART improves Hematological parameters, hence the improved level of PCV on those on ART than on those not on ART (Amegor, 2009(Amegor, et al, 2009Byomakesh et al, 2009). …”
Section: Discussionsupporting
confidence: 78%
“…Another study showed that neutropenia was associated with CD4 and platelet counts; and that thrombocytopenia was associated with country, gender, and chronic hepatitis B infection (16). However, studies in India (17) and Rwanda (5) did not find a significant correlation between thrombocytopenia and low CD4 count. The differences in the prevalence and risk factors could be attributed to demographic characteristics, geographical location, cut-off values used to define the cytopenias, and different stages of HIV illness in the study populations.…”
Section: Discussionmentioning
confidence: 93%
“…5 We encountered bicytopenia in 20% (24/120) of cases and only one pancytopenia. Byomakesh Dikshit et al, 11 encountered Pancytopenia in 6% (12/200) of cases in their cohort study. Sitalakshmi et al, 13 and Spivak J et al, 14 also reported fewer cases of pancytopenia in their HIV cohort study group.…”
Section: Thrombocytopenia In Hivmentioning
confidence: 99%